2021
DOI: 10.1021/acsomega.0c06008
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Syngas to Light Olefins through Fischer–Tropsch Synthesis over Fe–Zr Catalysts Modified with Sodium

Abstract: Fe−Zr−Na catalysts synthesized by coprecipitation and impregnation methods were implemented to investigate the promoting effects of Na and Zr on the iron-based catalyst for hightemperature Fischer−Tropsch synthesis (HTFT). The catalysts were characterized by Ar adsorption− desorption, X-ray diffraction, scanning electron microscopy, transmission electron microscopy, CO temperature-programmed desorption, H 2 temperature-programmed desorption, X-ray photoelectron spectroscopy, and Mossbauer spectroscopy (MES). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A series of Na impregnated Fe-Zr catalysts (Fe/Zr molar ratio = 100/15), prepared using the coprecipitation method, were used to evaluate the effect of Zr and Na on the physico-chemical properties of the catalysts and their catalytic performance in the hightemperature FT reaction [57]. The catalytic performances of the catalysts in FT reaction at 320 °C, 1.5 MPa, and H2/CO = 2, are shown in Table 2.…”
Section: Promoted Fe-based Catalystsmentioning
confidence: 99%
“…A series of Na impregnated Fe-Zr catalysts (Fe/Zr molar ratio = 100/15), prepared using the coprecipitation method, were used to evaluate the effect of Zr and Na on the physico-chemical properties of the catalysts and their catalytic performance in the hightemperature FT reaction [57]. The catalytic performances of the catalysts in FT reaction at 320 °C, 1.5 MPa, and H2/CO = 2, are shown in Table 2.…”
Section: Promoted Fe-based Catalystsmentioning
confidence: 99%
“…The introduction of zirconium shifts the hydrocarbon distribution to light hydrocarbons on FeMnxZr catalysts, so we hope that the molar ratio of alkenes to alkanes in the C 2 -C 4 hydrocarbons can be increased. According to previous research, [19][20][21] catalysts impregnated with an appropriate amount of Na increased the molar ratio of alkenes to alkanes in the C 2 -C 4 hydrocarbons and suppressed the CH 4 formation.…”
Section: Catalyst Performance In Ftsmentioning
confidence: 85%
“…Zhang et al 18 proposed that the addition of zirconium reduced the size of iron oxide particles, resulting in better FT activity and poorer chain growth capacity to form a C–C bond compared to Zr-free catalysts. Interestingly, Ma et al 19 found that Na increased CO dissociation adsorption and suppressed hydrogen adsorption, whereas Zr reduced the iron oxide crystallite size and stabilized the active phase. The introduction of Zr and Na resulted in higher FT activity and light olefin selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…They are utilized as vital building blocks to produce many essential end products in our daily lives (e.g., plastics, synthetic textiles, coatings, and solvents). 1,2 This crucial role of olefins rendered ethylene as the most produced hydrocarbon product worldwide. 3 As a result, enormous interest is oriented towards the production of olefins through a variety of petrochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Light olefins, especially ethylene, are economically valuable. They are utilized as vital building blocks to produce many essential end products in our daily lives (e.g., plastics, synthetic textiles, coatings, and solvents). , This crucial role of olefins rendered ethylene as the most produced hydrocarbon product worldwide . As a result, enormous interest is oriented towards the production of olefins through a variety of petrochemical processes. Most of these processes are petroleum-based, and with the rapid depletion of oil resources, the growing demand of light olefins has become a real challenge.…”
Section: Introductionmentioning
confidence: 99%